Studi tentang Peran Permainan terhadap Kemampuan Interaksi Sosial Anak Attention Deficit Hyperactivity Disorder (ADHD) dengan Teman Sebaya - Pambayun, Kumaralalitya (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: ADHD, a lack of ability to process information during social interactions with their environment, is caused by inhibited language skills and socializing with their peers. The low ability of social interaction means that ADHD children have to observe the behavior of their surroundings. Objectives: The researcher has an interest in conducting a study on whether there is a relationship in the role of play on the social interaction skills of children with ADHD typical children of the same age. Methods: This research uses a qualitative approach with a case study method with observation, interviews, documentation, and field notes, also by following Ry throughout the learning activities at school. Results: In the first month, Ry was still afraid and refused when asked to play with friends, but entering the IV month, there was a good change even though Ry only wanted to play with certain friends. In the last month, Ry has been able to invite his friends to play, by tapping their shoulders or pulling their hands, although occasionally he is still ignored by his friends. Conclusion: The role of play can help ADHD children's social interaction skills with their peers, as well as support from parents and accompanying teachers at school. Keywords : Games, Social Interaction, ADHD, Peer Friends